2007
DOI: 10.1126/science.1148735
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Lectin Analog for Biomimetic Disaccharide Recognition

Abstract: was measured with a physical property measurement system. The electrical resistivity shows the MIT at T c = 154 K on cooling ( Fig. 1) and exhibits large thermal hysteresis behavior indicating a first-order character of the MIT. Ca 1.9 Sr 0.1 RuO 4 crystals for scanning tunneling microscopy (STM), LEED, and HREELS measurements were mounted on the sample plates with conducting silver epoxy, and a small metal post was glued on top. The crystal was cleaved by knocking off the post in ultrahigh vacuum with a base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
197
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(208 citation statements)
references
References 30 publications
3
197
0
7
Order By: Relevance
“…Lectins, which are the most common class of sugar-binding proteins, bind monosaccharides with binding constants around 10 3 M −1 , 5,6 which corresponds to binding free energies on the order of 10k B T at physiological temperatures. For oligosaccharides the typical binding constants are higher, up to 10 6 -10 7 M −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lectins, which are the most common class of sugar-binding proteins, bind monosaccharides with binding constants around 10 3 M −1 , 5,6 which corresponds to binding free energies on the order of 10k B T at physiological temperatures. For oligosaccharides the typical binding constants are higher, up to 10 6 -10 7 M −1 .…”
Section: Introductionmentioning
confidence: 99%
“…7 This is still fairly low and constitutes a challenge to both biochemists and nature itself in the design of carbohydrate-recognizing proteins. 5 The binding sites in sugar-binding proteins often feature the flat side chains of the aromatic amino acids phenylalanine ͑Phe͒, tyrosine ͑Tyr͒, or particularly, tryptophan ͑Trp͒. 8 The extended active sites of cellulases, for example, contain several such residues spaced so as to interact with several sugar rings in cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…鉴于 PA 的 爆炸性大于 TNT, 且对人类和环境的危害性大 [14,15] , 人 们也开始开发聚合物类纯有机分子探针来检测 PA. 其 中, Trogler 课题组 [16,17] 最先从事这方面的工作, 他们从 化合物 1 出发, 利用其与金属锂反应, 分别合成不同的 硅杂环戊二烯类共轭聚合物 2 和 3 (Scheme 1), 它们都 可实现 PA 的检测. 进一步研究发现, 在硅杂环戊二烯共轭聚合物中引 入共轭的 C=C 双键等结构, 得到的系列荧光共聚物(如 化合物 4~7, 图 1), 同样也可检测 PA, 且猝灭效率更 好.…”
Section: 硅杂环共轭聚合物类unclassified
“…It was found that MC-1 exhibited good response of UV-vis and fluorescene toward glucosamine, but no response for glucose. Moreover, 1∶1 stoichiometric host-guest complexation of MC-1 for glucosamine was confirmed by the titration profile and electrospray ionization mass spectrometry (ESI-MS) spectrum, with an association constant (lg K ass ) being calculated as 7 …”
mentioning
confidence: 99%